(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
In today`s rapidly changing world the great improvements can be mentioned in Education also, especially, it can be seen in the sphere of teaching foreign languages. Communicative language teaching method has already become a vital part of English teaching methodology and it is still widely used by foreign language teachers. Besides, the topic of communicative language teaching is in the centre of attention and investigation of linguists.